CHARACTERISTICS, EPIDEMIOLOGY AND MODERN METHODS OF INVESTIGATION OF KLEBSIELLA PNEUMONIAE - Fotima Sh. Mamatmusaeva; Madina A. Mominova; Behzod A. Avazxonov; Gulzoda E. Halilova; Mamura F. Amatova (Central Asian Journal of Medicine, 2024)
Klebsiella pneumoniae carbapenemases (KPCs) were originally identified in the USA in 1996. Since then, these versatile b-lactamases have spread internationally among Gram-negative bacteria, especially K pneumoniae, although their precise epidemiology is diverse across countries and regions. The mortality described among patients infected with organisms positive for KPC is high, perhaps as a result of the limited antibiotic options remaining (often colistin, tigecycline, or aminoglycosides), In this Review, we summarise the epidemiology of KPCs across continents, and discuss issues around detection, present antibiotic options and those in development, treatment outcome and mortality, and infection control. In view of the limitations of present treatments and the paucity of new drugs in the pipeline, infection control must be our primary defence for now.